School bus drivers’ behavioural adaptation to speed limit devices for safe conveyance of private school students in Lagos State, Nigeria - Yisa, Mukaila Abiodun; Lemo, Olusiji Olaseni; Aderinto, Idowu Dare; Fasosin, Abioye David (INVOTEC, 2024)
Safety of passengers' lives and properties while traveling using vehicles majorly lies on behaviors of drivers. Hence, this study examined the school bus drivers’ behavioural adaptation to speed limit devices for safe conveyance of private school students in Lagos state. Descriptive survey research design was adopted for the study. The population comprised all 5,340 registered private schools in Lagos state. 400 school bus drivers were randomly sampled across all the twenty Local Government. An adapted questionnaire was used for data collection. Cronbach Alpha reliability technique was used to establish the internal consistency of the instrument and reliability coefficient of 0.83 was obtained. Data was analyzed using mean, standard deviation and t-test. Findings revealed that there is no significant difference between mean responses of mini and coaster school bus drivers on sensation seeking behaviour (t=-.769, p=.443), risk taking propensity (t=2.24, p=.026) and been cognitively indolent (t=.552, p=.581) towards speed limit devices and accident prevention for safe conveyance of private school students in Lagos state. It was recommended that Government, Ministry of Education and Transportation, in collaboration with the Federal Road Safety Corps, should thoroughly implement and enforce the usage of speed limit devices on all motorists to ensure safety.